Guidelines for day‐case surgery 2019: Guidelines from the Association of Anaesthetists and the British Association of Day Surgery. (8th April 2019) - Bailey, C. R.; Ahuja, M.; Bartholomew, K.; Bew, S.; Forbes, L.; Lipp, A.; Montgomery, J.; Russon, K.; Potparic, O.; Stocker, M.
Summary: Guidelines are presented for the organisational and clinical management of anaesthesia for day‐case surgery in adults and children. The advice presented is based on previously published recommendations, clinical studies and expert opinion.